ECONOMICAL ASPECTS OF DILUTED HF SOLUTIONS ON THE ANTIREFLECTIONS PROPERTIES OF THE FLOAT GLASS SURFACES - Wasylak, Jan; Zontek-Wilkowska, Joanna (European Scientific Journal, ESJ, 2014)
This work focuses on the development of a simple and low cost alternative to deposited antireflective coatings (ARC) through the use of a diluted HF wet chemical etching technique to form AR layers of silicon dioxide. Soda-lime-silica, low-iron glasses were used as the glass substrates. The float glass was etched for a variety of time intervals and with four different concentrations of HF solutions (0,5M, 1M, 5M, 10M). The optical properties were determined by UV-VIS spectroscopy. The microstructures were examined by SEM microscopy with EDAX analysis. The surface roughness after the wet chemical-etching was determined using an optical profilmeter.